Morphological, Molecular and Pollen Grain Investigations of Salix Species in Egypt (Baghdad Science Journal, 2021)
Genus Salix is among family Salicaceae, distributing in the northern hemisphere. It is represented in Egypt by two species (Salix mucronata and Salix tetrasperma). The classification of Salix at the generic and infra-generic levels is still outstanding. We have agreed to list the Egyptian species of this genus. We collected them during field trips to most Egyptian habitats; fresh and herbarium specimens were subjected to taxonomic revision based on morphological characters; scanning electron microscope (SEM) for pollen grains; isozyme analysis using esterase and peroxidase enzymes and genetic diversity using random amplified polymorphic DNA (RAPD). We recorded that both sexes of S. mucronata existed but there were only male trees from S. tetrasperma. SEM of pollen grain revealed that there were many differences between them. Also, the application of isozyme analysis giving 12 sex indicating bands. In addition, ten RAPD primers retrieved a total of 227 amplified bands (77 for female S. mucronata, 74 for male S. mucronata and 76 for male S. tetrasperma).